Is it scientifically justifiable to exclude wine and/or unfermented grape derivatives from the diet of consumers with or at risk of developing type-2 diabetes?. Issue 12 (18th November 2020) - Restani, Patrizia; Di Lorenzo, Chiara; Fradera, Ursula; Stockley, Creina S.; Teissedre, Pierre-Louis; Ruf, Jean-Claude; Iasiello, Barbara; Biella, Simone; Colombo, Francesca; Kosti, Rena I.
Abstract : This narrative review investigates whether low/moderate consumption of wine/grape's derivatives can be part of T2D individuals daily diet. Abstract : The abuse of alcoholic beverages has been associated with an increased risk of chronic-degenerative diseases, including diabetes mellitus, so that there is a general diffidence towards the low/moderate consumption of wine by individuals with type-2 diabetes (T2D) or at risk of developing it. This narrative review investigates by critical revision of the scientific literature whether wine/grape derivatives must be excluded or if their low/moderate consumption could be part of the daily diet of T2D individuals. Although further intervention studies on the consumption of alcoholic beverages and the development or control of T2D are needed, the burden of evidence suggests that low/moderate wine consumption could have beneficial effects.